Validity, reliability and responsiveness of the Turkish Version of the Munich Knee Questionnaire - Tayfur, Abdulhamit; Aslan, Mensure; Canli, Mehmet; Gürses, Ömer Alperen; Çakmak, Mehmet Fevzi; Yetiş, Mehmet; Ceylan, İsmail (Die Rehabilitation, 2025)
Self-reported surveys are an important part of a comprehensive assessment of clinical outcome. This cross-cultural adaptation study aimed to develop a Turkish version of the Munich Knee Questionnaire (MKQ-TR).A total of 200 participants including 112 people with various knee injuries (53.9±14.3 years, 68 males) and 88 healthy participants (30.0±11.9 years, 74 males) were recruited. We analyzed criterion validity with Pearson’s correlation coefficients and test-retest reliability with intraclass correlations coefficient (ICC). Standard error of measurement (SEM) and minimal detectable change (MDC) were investigated for absolute reliability.There were strong correlations between MKQ-TR and International Knee Documentation Committee (r=− 0.96, p<0.001) and Knee Injury and Osteoarthritis Outcome Score subscales (range for r=− 0.66 to − 0.96, all p<0.001). Reliability was excellent (ICC>0.90). The SEM results showed that absolute reliability ranged from good to doubtful (5.8–15.9%), hence acceptable. The MKQ-TR had an MDC of 6.14 and 29.7 as the cut-off point. The area under the ROC curve showed excellent (0.991) accuracy with 0.973 sensitivity and 0.977 specificity.MKQ-TR demonstrated excellent validity, reliability and accuracy to evaluate symptoms, pain, daily life activities, sports activities, physical function and quality of life in people with various knee injuries.
Keywords: Validity; reliability; responsiveness; knee; cross-cultural adaptation; patient reported outcome measure